Defining the contents of the foreign language teacher´s didactic competence - Camacho Delgado, Alfredo A.; Patterson Peña, Matilde (Varela Journal, 2012)
Undergraduate education of teachers of foreign languages in Cuba is continually subject to improvement processes responding to the development of pedagogical and linguistic sciences worldwide, and t o the increasing social educative demands that are made to in-service teachers. It has been a trend in many Cuban specialists to conceptualize didactic formation in terms of didactic competence. However, many specialists have questioned the possibility of designing a c urriculum in terms of competence and t here is also disagreement in relation to how to determine the content of didactic competence. This article intends to throw a bi t of light on the second issue posed above: How can teacher educators determine the content of the didactic competence of teachers of foreign languages? This, of course, with of improving what they do during the undergraduate teacher education studies.